Effectiveness of External Control of Public Finances in a Context of Decentralization: Evaluation of the Role of the Court of Auditors in the Provinces of the Democratic Republic of Congo from 2020-2025 - Carlos Mulopo; Glody Simisi Kimenika (International Journal of Innovative Science and Research Technology, 2026)
In a context of fiscal decentralization, external control of public finances plays a crucial role in enhancing transparency, accountability, and efficiency in budget management. In the Democratic Republic of Congo, the Court of Accounts serves as a key institution responsible for overseeing the regularity and performance of public financial management, particularly at the provincial level. This study aims to assess the effectiveness of the control exercised by the Court of Accounts in improving provincial budget management over the period 2020–2025. Using a methodological approach that combines documentary analysis and content analysis of official reports, the study examines control mechanisms, the level of implementation of audit recommendations, and their impact on budgetary performance. The findings reveal that, despite the existence of a formal institutional framework, the effectiveness of external control remains constrained by institutional capacity limitations, weak implementation of recommendations, and insufficient monitoring mechanisms. However, strengthening institutional capacities and improving follow-up processes could enhance budget efficiency at the provincial level.